EXPLORING THE EXEMPLARY ROLE OF SHEIKH HISAMUDDIN AS AN ISLAMIC PREACHER IN LAMONGAN, EAST JAVA: ANALYSIS OF LOCAL ISLAMIC HISTORY - Al Abdillah, M Irsyad; Amalina, Sharfina Nur; Adzani , Wanasa Rahmat Akbar; Sari, Dinda Novita (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2023)
Islamization in Indonesia has been through a different process in each region. The spread of Islam in Indonesia has occurred in several ways, including preaching (da'wah). Walisongo is an Islamic figure who plays a significant role in the spread of Islam, especially in Java. Besides Walisongo, other Islamic figures also preached to disseminate Islam in Indonesia. This research emphasizes the biography of Sheikh Hisammuddin and his contribution to Islamization, especially in Lamongan. The method used in the research is the historical method, which consists of five stages of research: topic selection, heuristic, source criticism, interpretation, and finally, the historiography stage. This research aims to comprehend the biography of Sheikh Hisamuddin, the model of the spread of Islam by Sheikh Hisamuddin in Lamongan, and the exemplary example of Sheikh Hisamuddin as a preacher of Islam. As a direct descendant of Sunan Ampel, he has his method of spreading Islam, such as a cultural approach, social approach, elements of tawhid, political methods, and Pondok Lelono. In addition to contributing to the development of Islam in Lamongan, Sheikh Hisamuddin has an exemplary attitude; he is a person who is diligent and pious, hardworking, wise, devout in worship, and firm.